Factors Contributing to Success and Guidelines for the Development of Waste Management in Nam Dam Subdistrict Thung Yang Daeng District Pattani Province. Factors Contributing to Success and Guidelines for the Development of Waste Management in Nam Dam Subdistrict Thung Yang Daeng District Pattani Province. - หะยีบูละ, อัสมา; วาเด็ง, นูรฟาร์; ซัยฟุดดีน , ซัยฟุดดีน; สุขเสนีย์, คมวิทย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research article are to 1) to study the factors on the success of the community's waste management in Nam Dam Subdistrict, Thung Yang Daeng District, Pattani Province 2) to study the guidelines for effective and appropriate community waste management in the context of the community. A case study of Nam Dam Subdistrict, Thung Yang Daeng District, Pattani Province. It is a qualitative research from 20 important information providers, including the President of the Nam Dam Subdistrict Administrative Organization, Thung Yang Daeng District, Pattani Province, 1 person, 1 deputy president of the Nam Dam Subdistrict Administrative Organization, 2 officials of the sub-district administrative organization, 16 people in the community and collect data with in-depth interviews and data analysis. The following steps have been carried out: 1) Read and understand all information 2) Separate important points 3) Group data by category 4) Summarize and explain with examples of the words of the information. The study found that 1. The success factors in the waste management of the Nam Dam sub-district community come from the implementation according to the framework of 5 important factors, namely community welfare, the working model of the committee, support from the agency, participation of the people and the budget. These factors help strengthen motivation, potential and resources, making the operation systematic and continuous, 2. Appropriate waste management guidelines result in 4 important results: a decrease in the amount of waste, more accurate waste separation behavior, making money from waste, and having a better environment and well-being, reflecting that waste management by focusing on sorting from the source and community participation can improve the quality of life concretely.